Estudos interacionais entre diferentes nanopartículas com estruturas supramoleculares de interesse biológico - Aguiar, Cínthia Das Dores (2022)
In the last few decades, a huge amount of research has emerged exploring the use of metallic nanoparticles (NPs) as drug delivery systems and quantum dots (QDs) as specific biomarkers. However, the mechanisms of interaction of these nanomaterials with the biological environment are still poorly understood and constitute a challenge for the development of a series of applications involving safe use. In this sense, the central objective of the work was to understand how different NPs affect and are affected by supramolecular structures of biological interest. Thus, to contribute with answers to this challenging question, the synthesis of gold nanoparticles (AuNPs) and cadmium telluride (CdTe) were conducted in the first step and characterized. In the second stage, we started the investigation of a method to evaluate the interaction between metallic NPs (AuNPs 4, 15, 40 and 60 nm) with Supported Lipid Bilayer Membrane (s-BLM), a platinum electrode, using the technique of cyclic voltammetry (CV). The s-BLM formed on the platinum electrode and was stable. Furthermore, it can be verified that AuNPs of different sizes induce different responses in the integrity of s-BLM according to the time of exposure to AuNP dispersions. To explore the in vivo application of quantum dots (QDs), we used the surface plasmon resonance (SPR) technique to investigate the kinetics and thermodynamics of interactions between human serum albumin (HSA) and CdTe QDs, functionalized with mercaptopropionic acid (MPA) or thioglycolic acid (TGA). Kinetic analysis showed that HSA-QD interactions involved the formation of transition complexes. Despite the structural similarities between MPA and TGA, the formation of by association of free HSA and QDs required 70% more energy and greater entropic gain than for the formation of . While dissociation required higher energy and lower entropy loss than dissociation . The stability of was independent of temperature and functionalizing group. However, enthalpic and entropic components were highly affected by CdTe@MPA QDs. Therefore, differences in QD functionalization and surface coverage densities can alter the HSA-QD interaction and, therefore, its application.